Langage, genre et sexualité - Auger, Nathalie (Éditions Nota Bene, 2011)
L'objectif de cet ouvrage est d'examiner les liens complexes entre langage, genre et sexualité. En adoptant un positionnement résolument critique, qui met l'accent sur les aspects historique, politique et social des pratiques langagières, cet ouvrage part de l'idée que le genre et l'identité sexuelle sont avant tout des constructions sociales et idéologiques qui trouvent une forme de matérialité, entre autres, dans les discours et les pratiques sociales. Nous croyons que ces processus langagiers participent à la formation des différences et des inégalités - sans toutefois en être l'unique cause -, qu'ils contribuent à la réification des catégories au même titre qu'ils permettent d'en créer de nouvelles.–Résumé de l'éditeur.
Section: 293 pages : illustrations (certaines en couleur), tableaux; 23 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; europe; france; francophonie; féminisme matérialiste; identités LGBTQIA2+; langue; lin2685; linguistique; premier cycle; queer; québec; régions géographiques; sciences humaines; sexualité; sociolinguistique; thématiques

Dancing on our turtle's back: Stories of Nishnaabeg re-creation, resurgence, and a new emergence - Simpson, Leanne (ARP Books, 2011)
Many promote Reconciliation as a "new" way for Canada to relate to Indigenous Peoples. In Dancing on Our Turtle's Back: Stories of Nishnaabeg Re-Creation, Resurgence, and a New Emergence activist, editor, and educator Leanne Simpson asserts reconciliation must be grounded in political resurgence and must support the regeneration of Indigenous languages, oral cultures, and traditions of governance. Simpson explores philosophies and pathways of regeneration, resurgence, and a new emergence through the Nishnaabeg language, Creation Stories, walks with Elders and children, celebrations and protests, and meditations on these experiences. She stresses the importance of illuminating Indigenous intellectual traditions to transform their relationship to the Canadian state. Challenging and original, Dancing on Our Turtle's Back provides a valuable new perspective on the struggles of Indigenous Peoples.
Keywords: amériques; approches et analyses; autochtones; canada; com5170; cours; cycles supérieurs; discipline; fem1000; fem3600; fem7000; féminisme autochtone; féminisme décolonial; linguistique; lit2815; lit3220; politique; premier cycle; réconciliation; régions géographiques; sciences humaines